Electronic structure and magnetic properties of bulk elements (Fe and Pd) and ordered binary alloys (FePd and Fe3Pd):TB-LMTO-ASA - Pandey, Suraj; Kaphle, Gopi Chandra; Adhikari, Narayan Prasad (BIBECHANA, 2014)
The binary alloys formed from the elements of Fe and Pd like FePd and Fe3Pd, have the strange electronic and magnetic properties, generally used in shape memory alloys, Computational chips, Medical purposes as well as modern technological uses. We used TB-LMTO-ASA Approach for the study of band structure and density of states of the transitional elements Fe and Pd and their ordered alloys FePd and Fe3Pd. We analyzed metallic and nonmetallic character and occupation of s, p and d electrons from the band structures and magnetic properties through the plot of density of states. Our findings show that all the elements and alloys bear metallic nature whereas bulk Palladium shows non magnetic behavior. Similarly Fe and both the ordered alloys FePd and Fe3Pd are found to be magnetic in nature with values 2.19μB, 3.49μB and 3.01μB respectively. These well agree with experimental as well as previous theoretical calculations. DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10381 BIBECHANA 11(1) (2014) 60-69